Estado nutricional e efeito da vitamina A na resposta imune frente à infecção por Leishmania Infantum - Maciel, Bruna Leal Lima (2013)
Nutritional status is an important determinant to the response against Leishmania infection, although few studies have characterized the molecular basis for the association found between malnutrition and the disease. Vitamin A supplementation has long been used in developing countries to prevent mortality by diarrheal and respiratory diseases, but there are no studies on the role of vitamin A in Leishmania infection, although we and others have found vitamin A deficiency in visceral Leishmaniasis (VL). Regulatory T cells are induced in vitro by vitamin A metabolites and are considered important cells implicated T CD4+ cell suppression in human VL. This work aimed to examine the correlation of nutritional status and the effect of vitamin A in the response against Leishmania infantum infection. A total of 179 children were studied: 31 had active VL, 33 VL history, 44 were DTH+ and 71 were DTH- and had negative antibody to Leishmania (DTH-/Ac-). Peripheral blood monuclear cells were isolated in a subgroup of 10 active VL and 16 DTH-/Ac- children and cultivated for 20h under 5 different conditions: 1) Medium, 2) Soluble promastigote L. infantum antigens (SLA), 3) All-trans retinoic acid (ATRA), 4) SLA + ATRA and 5) Concanavalin A. T CD4+CD25highFoxp3+, T CD4+CD25-Foxp3- and CD14+ monocytes were stained and studied by flow cytometry for IL-10, TGF-β and IL-17 production. Nutritional status was compromised in VL children, which presented lower BMI/Age and retinol concentrations when compared to healthy controls. We found a negative correlation between nutritional status (measured by BMI/Age and serum retinol) and anti-Leishmania antibodies and acute phase proteins. There was no correlation between nutritional status and parasite load. ATRA presented a dual effect in Treg cells and monocytes: In healthy children (DTH-/Ac-), it induced a regulatory response, increasing IL-10 and TGF-β production; in VL children it modulated the immune response, preventing increased IL-10 production after SLA stimulation. Furthermore, we found a positive correlation between BMI/Age and IL-17 production and negative correlation between serum retinol and IL-10 and TGF-β production in T CD4+CD25highFoxp3+ cells after SLA stimulus. Our results show a potential dual role of vitamin A in the immune system: improvement of regulatory profile during homeostasis and down modulation of IL-10 in Treg cells and monocytes during symptomatic VL. Therefore, the use of vitamin A concomitant to VL therapy might improve recovery from disease status in Leishmania infantum infection